UJI DOSIS TEPUNG BUAH SIRIH HUTAN (Piper aduncum L) TERHADAP MORTALITAS KUMBANG BUBUK (Sitophilus zeamais M) PADA JAGUNG DI PENYIMPANAN - Pasaribu, Pardi; Rustam, Rusli Rustam; Sutikno, Agus (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the dose of flour forest fruit betel (Piper aduncum L) that best powder beetle kills pests (Sitophilus zeamais M) on corn in storage. This research was conducted at the Laboratory of Plant Pests, Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted from April to June 2016. The research method implemented experimentally. This research was conducted in two series, the first carried out for 72 hours to observe the initial time of death, the daily mortality, Lethal time50, and total mortality, and the second after 5 weeks of infestation, which is observed is S. zeamais beetle population growth and shrinkage weight of corn by pests S. zeamais, using a completely randomized design (CRD), which consists of six treatments, with four replications thus obtained 24 experimental units. Each experimental unit infested as many as 10 animals         S. zeamais. The results showed that the dosage of flour betel vine forest at a dose of 8 g / 100 g of corn is the best dose to control S. zeamais with total mortality of 97.50%, the initial time of 5.50 hours of death, lethal time50 (LT50) during 21:00 hours. Keywords: S. zeamais M, betel fruit woods, corn